Effect of Continuity of Care on Drug-Drug Interactions. Issue 8 (August 2017) - Guo, Jiun-Yu; Chou, Yiing-Jenq; Pu, Christy
Abstract : Background: Drug-drug interaction (DDI) is a critical concern in health care systems because it is directly associated with patient outcomes and is generally preventable. However, few studies have been conducted on whether poor continuity of care (COC) is a determinant of DDIs and whether this effect varies by level of comorbidity. Patients with higher comorbidity normally require more complex treatment regimens than other patients, and hence their COC is more critical for ensuring the accuracy of their medication information. Objective: This study investigated the association between COC and DDI, with COC being measured as physician and site COC. The effect of comorbidities on DDI events was also analyzed. Methods: The Taiwan National Health Insurance claims data of ∼1, 000, 000 randomly selected insurance beneficiaries were used. Each person was longitudinally followed from 2005 to 2013. Negative nominal regressions were estimated to determine the effect of COC on DDI. Results: Higher COC was found to decrease the risk of DDI, and this risk reduction was even greater with physician COC and a higher Charlson comorbidity index. In the 1-year observation interval, patients exhibited a 3% reduction in DDIs for every 0.1 increment in their COC index. The ability of COC to reduce DDIs increased with the level of comorbidity. Similar results were observed when the observation interval was increased. Conclusions: Improving COC is critical for reducing DDIs. The effect of high-quality COC on the reduction of DDI is more significant for patients with higher levels of comorbidity; thus, they should be targeted to improve COC. Abstract : Supplemental Digital Content is available in the text.